2020
DOI: 10.3390/nu12102957
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Mediates the Relationship between Osteosarcopenia and Frailty: A Pathway Analysis

Abstract: Osteosarcopenia is associated with increased risk of adverse outcomes such as falls and fractures. Its association with frailty is less well-described, particularly in independent community-dwelling older adults. Although nutrition plays a crucial role in maintaining bone and muscle health, the complex relationship between osteosarcopenia and nutrition in the pathogenesis of frailty remains to be elucidated. In this cross-sectional analysis of 230 independent, community-dwelling individuals (mean age 67.2 ± 7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 38 publications
2
10
0
3
Order By: Relevance
“…Nutrition plays a critical role in the pathophysiology of frailty and the maintenance of bone 47 and muscle health. 45 , 48 One study suggested that malnutrition could play a role as a mediator of osteosarcopenia and sarcopenia in the development of frailty. 45 Furthermore, sufficient protein and vitamin D uptake in the elderly has been recommended for the prevention of muscle and bone loss as well as the maintenance of sufficient leg and grip strength.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutrition plays a critical role in the pathophysiology of frailty and the maintenance of bone 47 and muscle health. 45 , 48 One study suggested that malnutrition could play a role as a mediator of osteosarcopenia and sarcopenia in the development of frailty. 45 Furthermore, sufficient protein and vitamin D uptake in the elderly has been recommended for the prevention of muscle and bone loss as well as the maintenance of sufficient leg and grip strength.…”
Section: Discussionmentioning
confidence: 99%
“… 45 , 48 One study suggested that malnutrition could play a role as a mediator of osteosarcopenia and sarcopenia in the development of frailty. 45 Furthermore, sufficient protein and vitamin D uptake in the elderly has been recommended for the prevention of muscle and bone loss as well as the maintenance of sufficient leg and grip strength. 49 Associations between nutritional uptake, especially protein and the occurrence of post-operative surgical complications in patients with hip fractures 50 , 51 and the importance of nutritional status for the improvement of activities of daily living and the incidence of subsequent fracture in DRF patients 52 have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrition is an integral part of frailty management. 30 For individuals with sarcopenia or weight loss, providing oral nutritional supplements to undernourished adults can result in weight gain and restoration of function. Multiple factors play a role in weight loss, including medications, depression, malnourishment, and poor dentition.…”
Section: Nutritionmentioning
confidence: 99%
“…Dolaylı olarak metabolik hız ve KMY'nin düşüşüne neden olmaktadır. 36 Kas-iskelet sistemi hastalıklarının önlenmesi için bireyin enerji dengesinin stabil tutulması gerekmektedir. 21 Yaşlanma ile enerji harcamasında oluşan azalma enerji tüketimindeki azalma ile dengelenerek, ideal vücut ağırlığı sürdürülmeli ve şişmanlık, vücut yağının artması önlenmelidir.…”
Section: Beslenmeunclassified